A nuclear membrane-derived structure associated with Atg8 is involved in the sequestration of selective cargo, the Cvt complex, during autophagosome formation in yeast. Issue 3 (4th March 2019) - Baba, Misuzu; Tomonaga, Sachihiko; Suzuki, Masato; Gen, Maeda; Takeda, Eigo; Matsuura, Akira; Kamada, Yoshiaki; Baba, Norio
ABSTRACT: Macroautophagy (hereafter autophagy) is a conserved intracellular degradation mechanism required for cell survival. A double-membrane structure, the phagophore, is generated to sequester cytosolic cargos destined for degradation in the vacuole. The mechanism involved in the biogenesis of the phagophore is still an open question. We focused on 4 autophagy-related (Atg) proteins (Atg2, Atg9, Atg14, and Atg18), which are involved in the formation of the phagophore in order to gain a more complete understanding of the membrane dynamics that occur during formation of the autophagosome. The corresponding mutants, while defective in autophagy, nonetheless generate the membrane-bound form of Atg8, allowing us to use this protein as a marker for the nascent autophagosome precursor membrane. Using electron microscopy (EM), we discovered in these atg mutants a novel single-membrane structure (~120 to 150 nm in size). Electron tomography revealed that this structure originates from a part of the nuclear membrane, and we have named it the alphasome. Our data suggest that the alphasome is associated with Atg8, and sequesters selective cargo, the Cvt complex, during autophagy. Abbreviations: 3D: three-dimensional; AB: autophagic body; AP: autophagosome; Atg: autophagy-related; Cvt: cytoplasm-to-vacuole targeting; EM: electron microscopy; IEM: immunoelectron microscopy; L: lipid droplet; N: nucleus; NM: nuclear membrane; PAS: phagophore assembly site; PE: phosphatidylethanolamine; prApe1: precursor aminopeptidase I; rER: rough endoplasmic reticulum; TEM: transmission electron microscopy; V: vacuole; VLP: virus-like particle;